Fifteen-minute consultation: Recognising primary immune deficiencies in children. Issue 5 (7th February 2019) - Wekell, Per; Hertting, Olof; Holmgren, Daniel; Fasth, Anders
Abstract : Children with primary immunodeficiency syndromes present with broad variation of clinical features and the consequences are often severe if not promptly recognised. Here, support is provided for the general paediatrician to recognise primary immunodeficiencies among the many children they meet in their clinical practice.